Value-Added of Processed Cocoa Seed: A Case Study In CV. Putra Mataram, Polewali Mandar Regency - Fattah, Muhammad Arifin; Arifin, Arifin; Sadat, Mohammad Anwar; Azisah, Azisah; Pata, Abdul Asis (Universitas Negeri Gorontalo, 2023)
The purpose of this study was to analyze the added value of processed cocoa bean products in chocolate bars and powder at CV. Putra Mataram, Poolewali Mandar Regency. This research was conducted at CV. Putra Mataram, Polewali Mandar Regency in July to August 2022. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis method used in this research is descriptive quantitative. The data were analyzed by the Hayami method. The results showed the added value obtained by CV. Putra Mataram from processing cocoa beans into chocolate bars and cocoa powder for one production, which is IDR. 527,640, with details for chocolate bars of IDR. 406,640 and cocoa powder for IDR. 121,000. The added value and benefits obtained by CV. Putra Mataram from the processing of cocoa beans is larger than chocolate bars compared to cocoa powder. Therefore chocolate bars need to be prioritized to produce larger quantities to increase profits.